Processing and characterization of a polylactic acid/nanoclay composite for laser sintering. Issue 11 (5th November 2015) - Bai, Jiaming; Goodridge, Ruth D.; Hague, Richard J.M.; Okamoto, Masami
Abstract : In this work, the feasibility of processing polylactic acid (PLA) and a PLA/nanoclay composite by laser sintering (LS) were investigated. The morphology of both the PLA and PLA/nanoclay powder was examined by scanning electron microscopy. LS process parameters, especially powder bed temperature, laser power, and laser scan count were studied. The effect of the addition of nanoclay on the thermal and flexural properties of LS PLA parts was examined. The results showed that PLA/nanoclay required a lower processing powder bed temperature compared with neat PLA. Under the same powder bed temperature, PLA/nanoclay parts exhibited an improvement in flexural modulus compared with neat PLA. Flexural modulus was increased significantly with double scan for both neat PLA and PLA/nanoclay LS parts. POLYM. COMPOS., 38:2570–2576, 2017. © 2015 Society of Plastics Engineers